Effect of Different Mulches and Planting Beds On Growth and Yield of Bitter Gourd in Coastal Saline Soils (Bangladesh Journal of Agricultural Research, 2023)
A field experiment was carried out in coastal saline soils of Bangladesh in 2018, 2019 and 2020 to evaluate the effect of different kinds of mulches and planting beds to reduce salt accumulation in the soil and to increase the yield of bitter gourd. The experiment was laid out in a factional randomized complete block design having two kinds of mulches: viz. rice straw mulch and polythene mulch along with no mulch control and three kinds of planting beds: viz. convex bed, flat bed and concave bed. The polythene mulch treatment had highest fruit yield of 21.86, 27.20 and 20.49 t ha-1, respectively followed by rice straw mulch and no mulch control treatment in 2018, 2019 and 2020, respectively. Polythene mulch reduced electrical conductivity of soil by 31% and soil sodium content by 42% compared to no mulch treatment. Polythene mulch also increased soil temperature and gravimetric soil moisture content which promoted plant growth. The convex bed method produced highest mean fruit yield of 18.37, 20.06 and 15.18 t ha-1 followed by the flat bed and concave bed method in the year 2018, 2019 and 2020, respectively. Combined use of polythene mulch and convex bed planting could provide greatest benefit to the farmers. The polythene mulch along with convex bed planting is therefore, recommended to get higher yield of bitter gourd and to reduce detrimental effect of salt on crop in coastal saline soils.Bangladesh J. Agril. Res. 46(1): 71-87, March 2021